Mice expressing a human K(ATP) channel mutation have altered channel ATP sensitivity but no cardiac abnormalities. - Clark, R; Männikkö, R; Stuckey, D; Iberl, M; Clarke, K; Ashcroft, F (2012)
AIMS/HYPOTHESIS: Patients with severe gain-of-function mutations in the Kir6.2 subunit of the ATP-sensitive potassium (K(ATP)) channel, have neonatal diabetes, muscle hypotonia and mental and motor developmental delay-a condition known as iDEND syndrome. However, despite the fact that Kir6.2 forms the pore of the cardiac K(ATP) channel, patients show no obvious cardiac symptoms. The aim of this project was to use a mouse model of iDEND syndrome to determine whether iDEND mutations affect cardiac function and cardiac K(ATP) channel ATP sensitivity. METHODS: We performed patch-clamp and in vivo cine-MRI studies on mice in which the most common iDEND mutation (Kir6.2-V59M) was targeted to cardiac muscle using Cre-lox technology (m-V59M mice). RESULTS: Patch-clamp studies of isolated cardiac myocytes revealed a markedly reduced K(ATP) channel sensitivity to MgATP inhibition in m-V59M mice (IC(50) 62 μmol/l compared with 13 μmol/l for littermate controls). In vivo cine-MRI revealed there were no gross morphological differences and no differences in heart rate, end diastolic volume, end systolic volume, stroke volume, ejection fraction, cardiac output or wall thickening between m-V59M and control hearts, either under resting conditions or under dobutamine stress. CONCLUSIONS/INTERPRETATION: The common iDEND mutation Kir6.2-V59M decreases ATP block of cardiac K(ATP) channels but was without obvious effect on heart function, suggesting that metabolic changes fail to open the mutated channel to an extent that affects function (at least in the absence of ischaemia). This may have implications for the choice of sulfonylurea used to treat neonatal diabetes.